Support for innovative on-street parking policies: empirical evidence from an urban neighborhood - Kirschner, Franziska; Lanzendorf, Martin (Journal of transport geography, 2020)
Municipalities and planners often hesitate to implement restrictive parking policies because residents regularly oppose any changes to on-street parking space. Residential parking is one key factor of parking management because its location and availability influence a household's car ownership and use. Moreover, as more residents regularly use other means of transportation that need space and infrastructure in the urban realm, and as parking takes up a vast amount of land, municipalities are considering the reuse of on-street parking space for other purposes. As public acceptability is a precondition for the successful implementation of a proposed policy, our empirical analysis investigates to what extent residents support restrictive and demand-oriented on-street parking policies in the dense, highly urbanized neighborhood of Frankfurt-Bornheim, Germany (N = 1027). Surprisingly, despite some variations, the majority of the residents in our survey are in favor of the policy options suggested. Support for the demand-oriented policies (extension of bicycle infrastructure, improved sharing supply and mobility hubs, neighborhood garages, and improved public transit supply) is higher than the acceptance of the restrictive policies, and of policies that are a combination of restrictive and demand-oriented policies. However, surprisingly, a majority is still in favor of many of these (extension of parking fees and parking restrictions, and reuse of parking space for better livability). Furthermore, we classify residents who live in a household with private cars into the stage model of self-regulated behavior change to analyze their intention towards a reduction in private car use. Results from linear regression analyses indicate that residents who have intentions to change their behavior towards car use reduction assess the policy options more similarly to car-free households and regular bike users, and not like the other car-owning households. The findings suggest that while the residents support financial-related policies the least, they are more receptive towards parking policies than policy makers and planners assume if the reuse of parking lots creates space for other users or if it increases the quality of life, for instance, by adding bike lanes, wider sidewalks or greenery. Hence, a combination of restrictive and demand-oriented on-street parking policies results in high acceptance among residents, and the communication from municipalities regarding the implementation of the different policies needs to vary depending on the kind of household. •We analyze residents' support for restrictive and demand-oriented parking policies.•Findings suggest that residents are in favor of most parking policies.•We classify residents into the stage model of self-regulated behavior change.•Residents in the postactional stage assess the policies like car-free residents.